Thermal radiation and Joule heating effects on a magnetohydrodynamic Casson nanofluid flow in the presence of chemical reaction through a non-linear inclined porous stretching sheet - Goud, B. Shankar; Reddy, Y. Dharmendar; Rao, V. Srinivasa (Journal of Naval Architecture and Marine Engineering, 2020)
The present study explores the thermal and Joule heating effect of Casson nanofluid flow with chemical reaction over an inclined porous stretching surface. The results of heat source/sink, viscous dissipation, and suction are regarded. The new physical governing equations of partial differential flow equations are converted into nonlinear ordinary differential equations and are numerically resolved employing the implicit finite difference technique. The influence on velocity, temperature, and concentration fields of many flow variables are addressed. The numerical and graphical findings are defined for the numerous related attentiveness flow parameters. The empirical data reported are compared with the published outcomes.